Ano-rectal malformations - Falco de Torres, Editta; Chavarría, Oscar (Cirugía del Uruguay, 1979)
The paper contains a review of 40 cases of ano-rectal malformations treated at the Pereira Rossell Hospital. An analysis thereof indicates the need of early detection, evaluation of type of malformation and identification of associated malformations. Stress in laid on factors which determine continence and on the need to establish therapy which respect the musculi puborectalis.